Inside Cover Image, Volume 3, Issue 6. (14th October 2016) - Zhang, Ke; Kimball, John S.; Running, Steven W.
Abstract : The inside cover image, by Ke Zhang et al., is based on the Advanced Review A review of remote sensing based actual evapotranspiration estimation, DOI: 10.1002/wat2.1168 Abstract : The inside cover image, by Ke Zhang et al., is based on the Advanced Review A review of remote sensing based actual evapotranspiration estimation, DOI: 10.1002/wat2.1168